Transparency in Village Fund Management in Bontocani District Bone Regency - Andi Akhdar Darwin; Muh Nur Sadik; Syahribulan Syahribulan; Muh Tang Abdullah (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
Transparency is perceived as the disclosure of information to the public regarding the process or performance of the government. This study aims to analyze the application of the principle of transparency in the management of village funds in Bontocani District, Bone Regency. The research method uses a qualitative approach with a case study type. The data collection process includes the stages of observation, in-depth interviews, and documentation. Data sources consist of primary and secondary data. The stages of data analysis include data reduction, data presentation and drawing conclusions. The results showed that the transparency in the management of village funds in the Bontocani District was quite good in its implementation, but still needed to be improved. There is still some information that is not known by the community, even though all information regarding the management of village funds should be transparent. The village government has implemented the applicable rules and regulations.